Deskripsi Stres Peserta Didik Saat Mengikuti Ujian Nasional pada Jenjang Pendidikan Sekolah Menengah Atas - Paul Arjanto (Program Studi Bimbingan dan Konseling, Universitas Pattimura, 2020)
The national exam raises various demands. Students feel they are required to achieve an achievement. These demands can put pressure on the potential to cause stress on students. The stress experienced by students at a mild level actually makes students excited to learn in the face of national exams, but at a later stage stress can cause complaints from students. The research objective was to identify the stress level of students before the secondary education level national exam. This research uses descriptive research with a quantitative approach (descriptive research). Research instrument to measure stress level based on symptoms / symptoms arising from individuals experiencing stress using the DASS Instrument (depression anxiety stress scale). The results showed that 8% of students experienced severe stress, 24% of students experienced moderate stress, 50% of students experienced stress at a mild level and 18% of students experienced stress at a normal level and no students experienced stress at a normal level. very heavy. Researchers suggest: 1) increasing the number of research subjects so that they can generalize research data, 2) controlling for other factors that are thought to affect students' stress levels such as social support from family, the role of guidance teachers in schools, and the personalities of students who are vulnerable to stress.